2006
DOI: 10.1007/s10562-006-0031-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Reverse Water–gas Shift over La2NiO4 Catalyst by Cw-cavity Enhanced Absorption Spectroscopy During CH4/CO2 Reforming

Abstract: Reverse water-gas shift (RWGS) reaction over La 2 NiO 4 catalyst was investigated during CH 4 /CO 2 reforming by continuous wave cavity enhanced absorption spectroscopy, a sensitive absorption technique. The results indicated that the RWGS reaction promoted the conversion of CO 2 and decreased the partial pressure of hydrogen. By proper adjustment of the pressure of the reaction system, it is possible to suppress the occurrence of RWGS reaction and increase the selectivity of CH 4 /CO 2 reforming. The intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 41 publications
3
6
0
Order By: Relevance
“…The results of CO 2 -TPD analysis verified that the introduction of La 2 O 3 results in the retention of CO 2 in the 500-600°C range due to the formation of La 2 O 2 CO 3 . 27 The adsorption and desorption of CO 2 in the 350-650°C range is catalytically more relevant because the EBDH reaction occurs in the 500-600°C range. Figure 6 showed the NH 3 -TPD spectra of different samples.…”
Section: Xrd Characterizationmentioning
confidence: 99%
“…The results of CO 2 -TPD analysis verified that the introduction of La 2 O 3 results in the retention of CO 2 in the 500-600°C range due to the formation of La 2 O 2 CO 3 . 27 The adsorption and desorption of CO 2 in the 350-650°C range is catalytically more relevant because the EBDH reaction occurs in the 500-600°C range. Figure 6 showed the NH 3 -TPD spectra of different samples.…”
Section: Xrd Characterizationmentioning
confidence: 99%
“…Under the SJE condition, we do not detect C 2 H 4 þ , C 2 H 6 þ , and C 6 H 6 þ but CHO þ in a span of 165 min (Figure 2c). The identity of CHO þ was confirmed before through the detection of 13 CHO þ when 13 CH 4 (rather than 12 CH 4 ) was introduced to the reactor under SJE condition. 17 As suggested, CHO is formed as a result of CH x interaction with oxygen on the surface of 3%Mo/HZSM-5, and the decomposition of HCO gives CO and H. 12 Apparently, it is hard to detect the CHO intermediates under normal condition.…”
Section: Mechanism Of H 2 O Action and Introduction Mode Of H 2 O/ch mentioning
confidence: 87%
“…12,13 With rapid departure of hydrogen and aromatics from catalyst, product/catalyst interaction is limited and coke formation is not serious. In CH 4 /CO 2 reforming reactions over La 2 NiO 4 and 10%NiO/ CeO 2 -La 2 O 3 catalysts, we found that CO 2 and CH 4 conversions under SJE condition were significantly higher than those at equilibrium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon dioxide (CO 2 ) reforming of methane to synthesis gas attracts ever-growing interest from both environmental and industry aspects [1][2][3][4][5][6]. It provides a practical and effective way for the utilization of the two major greenhouse gases (CO 2 and methane) [2].…”
Section: Introductionmentioning
confidence: 99%